2021
DOI: 10.21203/rs.3.rs-234367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The prevalence and socio-demographic risk factors of coexistence of stunting, wasting and underweight among children under five years in Bangladesh

Abstract: Background Childhood malnutrition in all its forms is a significant public health challenge for developing countries like Bangladesh. There is a gap in knowledge of the coexistence of various forms of malnutrition among children under five years (under-5) in Bangladesh. This study aims (i) describe prevalence and risk factors for the coexistence of stunting, wasting and underweight among children under-5 in Bangladesh. Methods This study included 6,610 and 7,357 under-5 children from Bangladesh Demographic H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…The study showed that prevalence of stunting children was more common among male than female children but statistically was not significant. This founding similar to other studies that documented boys more common than girls in the prevalence of stunted children [12], [13], [14]. To date, it is unclear what social or biological reason might account for this difference [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study showed that prevalence of stunting children was more common among male than female children but statistically was not significant. This founding similar to other studies that documented boys more common than girls in the prevalence of stunted children [12], [13], [14]. To date, it is unclear what social or biological reason might account for this difference [14].…”
Section: Discussionsupporting
confidence: 91%
“…This means that the coexistence of stunting, wasting, and underweight in our subject participants already exists. Studies in Bangladesh found that one in thirty-five children had coexisted with stunting, wasting, and underweight [13].…”
Section: Discussionmentioning
confidence: 99%
“…Dalam penelitian lain, stunting ditemukan lebih tinggi pada kelompok usia lebih tua yaitu 24-35 bulan di Uganda 66 , Bangladesh 67 , Nigeria 68 , dan Tanzania 69 . Bahkan, penelitian di Afrika Timur 32 , dan Bangladesh 67,70,71 , kejadian stunting lebih banyak terjadi pada kelompok usia 36-47 bulan.…”
Section: Hasil Dan Pembahasanunclassified